JENIS DAN POPULASI LALAT BUAH (Bactrocera sp.) PADA TANAMAN CABAI KERITING (Capsicum annuum L.) DI KOTA TOMOHON - Erionata Manoi; Jimmy Rimbing; Ventje Memah (Universitas Sam Ratulangi, 2016)
SUMMARYThe study aims to determine the type and population of Bactrocera sp. in pepper curls inTomohon. Results are expected to be used as consideration in the preparation of pest controlstrategies Bactrocera sp. in pepper curls in the future akang come. The experiment was conducted incropping chilli curls on three Subdistrict namely Rurukan, Kakaskasen and Wailan. Research wasconducted during Â± 3 months, ie April to June 2016. The study used survey methods at severalcenters planting chilli curls in Tomohon, then set the three villages as a location for research or as asampling. Criteria for the study site by the presence of old crop curly chili fruitful. Sampling usingMethod Diagonal slices are laid randomly trap fruit flies in each sub - sampling sites. Sampling wasdone by taking the imago Bactrocera sp. trapped, then the sample was collected in a bottlecontaining pure alcohol. Samples are labeled according to location and time of uptake, then taken tothe Laboratory of Entomology and Pest Plants, Faculty of Agriculture, University of Sam Ratulangi.Sampling was performed 5 times with intervals of 6 days. The results showed that there are twotypes and pest populations Bactrocera sp. at various research sites that Bactrocera dorsalis (Hendel)and Bactrocera umbrosa (Fabricus) with a total population of 4484 individuals.Key word : Cabai Keriting, Bactrocera sp.